Liberating Justice: Interpreting Luke’s Parable of the Widow and the Judge in Light of Norm Theory and the Experience of Modern Women in Politics - Ellison, Lauren (Feminist theology, 2025)
This article analyzes sociological underpinnings and implications of Luke’s parable of the widow and judge (Lk. 18.2-5) by reading it through the lens of norm theory. It uses the predicament of modern women politicians as norm violators within masculinized political spaces to shed light on the interaction between the widow and the judge. The judge, like male politicians interested in maintaining their privilege within normative structures, responds negatively to the widow’s display of agency. The widow, like today’s female politicians, is a “trendsetter,” a person who defies convention to spearhead new behavior. Her resistance to social sanctions models successful deviance and serves as an example to the parable’s audience of how to actively resist maladaptive social norms in order to shift society toward greater justice.